2008
DOI: 10.1007/s00414-008-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel transcript profiling of diffuse alveolar damage induced by hyperoxia exposure in mice: normalization by glyceraldehyde 3-phosphate dehydrogenase

Abstract: Under mechanical ventilation with high-inspired oxygen concentration, diffuse alveolar damage was found to take place in some patients. To clarify the molecular pathophysiology of this condition, we investigated the time course of gene expression changes induced by hyperoxia exposure in mouse lung using real-time quantitative polymerase chain reaction (qPCR). Our results normalized by glyceraldehyde 3-phosphate dehydrogenase showed that mRNA levels of cysteine rich protein 61 (CYR61) and connective tissue grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…As time after injury increased, the expression levels of sTnI mRNA gradually became stable. The findings on sTnI mRNA expression are almost identical to the results obtained by Shimada et al [27], who reported that the expression levels of TnI mRNA decreased following diffuse alveolar damage.…”
Section: Discussionsupporting
confidence: 91%
“…As time after injury increased, the expression levels of sTnI mRNA gradually became stable. The findings on sTnI mRNA expression are almost identical to the results obtained by Shimada et al [27], who reported that the expression levels of TnI mRNA decreased following diffuse alveolar damage.…”
Section: Discussionsupporting
confidence: 91%
“…The clinical association of CTGF with BPD is best established by studies demonstrating increased CTGF concentrations in bronchoalveolar lavage fluid from preterm infants developing BPD (5) and increased CTGF expression in lung tissues of infants who died of BPD (6). Multiple studies have examined the potential role of CTGF in experimental BPD and demonstrated that increased CTGF expression is associated with chronic hyperoxia as well as mechanical ventilationinduced lung injury in neonatal rodents (6)(7)(8)(9)(10). Recent studies from our laboratory utilizing genetic gain-of-function and biological loss-of-function approaches have provided compelling evidence that a novel signaling network orchestrated by CTGF plays an important role in BPD pathogenesis (6,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen also causes oxidative pulmonary injury at a high concentration during artificial respiration [111]. These specific toxicities cannot be detected by morphology in acute death cases, but may be detectable by molecular biological procedures.…”
Section: Miscellaneousmentioning
confidence: 96%